Beyond the Numbers: Exploring the Landscape of Adolescent Hypertension in Contemporary Literature - Cecilia Amponsem-Boateng; Jonathan Boakye- Yiadom; Ninon P. Amertil; Augustine Kwakye Sampah (Adventist University of Africa, 2024)
This literature review delves into the escalating global health concern regarding hypertension among adolescents, with a particular focus on the unique challenges faced by African youth. Initially associated with aging, hypertension is now prevalent among teenagers, necessitating a shift in focus and understanding of the global health landscape. This manuscript highlights the prevalence of hypertension among adolescents in Africa, the risk factors for hypertension among adolescents in Africa, the consequences of hypertension in adolescence, and interventional strategies.